ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN UMUM KONVENSIONAL DAN PERBANKAN SYARIAH PERIODE 2011-2015 - Wijaya, Luh Dita Dian; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
The goal of this study is determining the difference of financial performance between conventional banks and Islamic banks as seen from its financial ratios. Financial ratios used are CAR, NPL, ROA, BOPO, and LDR. Data from this study obtained by looking at the financial statements of listed banks Financial Services Authority (FSA) with a population of 53 conventional banks and 10 Islamic banks. The samples used as many as 8 conventional banks and Islamic banks 8, with nonprobability sampling method. Data collection method used is a non-participant observation method. Analysis of the data using two different test average (Independent Sample t-Test) with SPSS.Based on the research, concluded there is a difference in the financial performance of conventional banking and Islamic banking is seen on financial ratios CAR, NPL, ROA, BOPO, and LDR.
Keywords: CAR, NPL, ROA, BOPO, and LDR